The challenge of enterprise/innovation: a case study of a modern university. Issue 1 (2nd January 2020) - Jones, Gill; Fleming, Scott; Laugharne, Janet
ABSTRACT: In the prevailing economic and political climate for Higher Education a greater emphasis has been placed on diversifying the funding base. The present study was undertaken between 2012 and 2014 and addressed the implementation of an approach to the transformation of one academic school in a medium-sized modern university in Wales to a more engaged enterprise culture. A multimethod investigation included a bi-lingual (English and Welsh) online survey of academic staff and yielded a 71% response rate (n = 45). The findings informed a series of in-depth interviews (n = 24) with a representative sample of those involved in enterprise work (support staff, managers, senior managers), and those who were not. The results provided the platform for the 'S4E model' for effective engagement with enterprise: (1) Strategic significance for Enterprise, (2) Support for Enterprise, (3) Synergy for Enterprise, and (4) Success for Enterprise. The outcomes of the research and the recommendations from it have potential to inform practice in other academic schools within the university and, in a wider context, within other Schools of Education regionally, nationally and internationally. Its original empirical exploration of enterprise within education studies is a significant contribution to that body of knowledge.